PEMANFAATAN TANAMAN TOGA KUNYIT UNTUK MEMBUAT MINUMAN SEGAR SINOM DI DESA SAWOTRATAP, KECAMATAN GEDANGAN, KABUPATEN SIDOARJO - juliani pudjowati; Mayke Puspita Anindika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Sinom is a traditional drink or herbal medicine made from two different types of spices, turmeric and tamarind. In Indonesia, these two spices can not only be used as cooking spices, but also processed into drinks known to be efficacious for health. Sinom has long been known as a drink that has various health benefits which are believed to boost the immune system without excessive side effects. This is due to the content of curcumin in turmeric which acts as a natural antioxidant and anti-inflammatory. Given the very large content, the KKN students in Sawotratap Village provide one of the programs, namely by jointly making the basic ingredients in making the herbal drink sinom made of turmeric and tamarind and of course has economic value in the economic development of the Sawotratap Village community. The big benefit that can be taken from this activity program is developing entrepreneurial innovations for the Sawotratap village community with a creative economy as an effort that can be used as a form of improving the community's economy. The existence of turmeric and tamarind which was originally only sold in traditional markets, with this processed product, turmeric and tamarind can be used as a business idea for the Sawotratap village community and is expected to be known by the wider community